2012
DOI: 10.1007/s11538-012-9784-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hindered Transport on the Development of Platelet Thrombi Under Flow

Abstract: Vascular injury triggers two intertwined processes, platelet deposition and coagulation, and can lead to the formation of an intravascular clot (thrombus) that may grow to occlude the vessel. Formation of the thrombus involves complex biochemical, biophysical, and biomechanical interactions that are also dynamic and spatially-distributed, and occur on multiple spatial and temporal scales. We previously developed a spatial-temporal mathematical model of these interactions and looked at the interplay between phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 44 publications
4
76
0
Order By: Relevance
“…Hemostatic thrombi halt both forms of loss by restricting movement within and across the thrombus microenvironment. [10][11][12][13][14][15] Consistent with this role, we have previously shown that thrombi formed from human blood flowing over a collagen/tissue factor (TF) surface have a Darcy permeability approaching that of intact endothelium (k 5 2 3 10 214 cm 2 ). 5 Since plasma and platelets are the source of numerous coagulation factors, [16][17][18] growth factors, [19][20][21][22] and mediators of inflammation, 23,24 transport properties at the injury site can also be viewed as regulators of wound healing and recovery.…”
Section: Introductionmentioning
confidence: 71%
“…Hemostatic thrombi halt both forms of loss by restricting movement within and across the thrombus microenvironment. [10][11][12][13][14][15] Consistent with this role, we have previously shown that thrombi formed from human blood flowing over a collagen/tissue factor (TF) surface have a Darcy permeability approaching that of intact endothelium (k 5 2 3 10 214 cm 2 ). 5 Since plasma and platelets are the source of numerous coagulation factors, [16][17][18] growth factors, [19][20][21][22] and mediators of inflammation, 23,24 transport properties at the injury site can also be viewed as regulators of wound healing and recovery.…”
Section: Introductionmentioning
confidence: 71%
“…Computational studies that recapitulate platelet accumulation and transport may prove helpful in this regard, especially as the simulations become even more refined. 10,17,[45][46][47][48][49][50] …”
Section: Is Any Of This Clinically Relevant?mentioning
confidence: 99%
“…In the medium to large arteries, tens of millions to billions of platelets can pass through the artery each second [39], making direct tracking of physiological platelet counts computationally infeasible in such domains. Instead, some researchers have utilized an Eulerian framework, in which concentrations of activated platelets are tracked as a continuum quantity [40][41][42][43][44]. To date, these Eulerian frameworks have been applied to the biochemical activation of platelets, and use of such methods to investigate biomechanical activation has been less explored.…”
Section: Introductionmentioning
confidence: 99%